A Bridge of Light: Toward Chinese and Western Medicine Perspectives Through Ultraweak Photon Emissions. (June 2019) - Yang, Meina; Van Wijk, Eduard; Pang, Jingxiang; Yan, Yu; van der Greef, Jan; Van Wijk, Roeland; Han, Jinxiang
The gap between Western medicine and traditional Chinese medicine (CM) is closely related to the diversity in culture, philosophy, and scientific developments. Although numerous studies have evaluated the efficacy of acupuncture, the gap in explanatory disease models has not been bridged so far. Developments in research of ultraweak photon emission (UPE) and organized dynamics of metabolism and its relationship with technological advances in metabolomics have created the conditions to bring the basics of the medicines of the West and East together which might open the avenue for a scientific dialogue. The paper discusses (1) the UPE in relation to Qi energy, meridians and acupuncture points in CM, (2) the biochemical explanation of photon emission of living systems in Western biomedicine, and (3) the progress in research on the large-scale organization and dynamics of the metabolic network including photon metabolism.